1990
DOI: 10.1128/jvi.64.11.5383-5388.1990
|View full text |Cite
|
Sign up to set email alerts
|

In vivo polyclonal B-lymphocyte activation elicited by murine viruses

Abstract: Viruses such as lactate dehydrogenase-elevating virus and adenovirus induce in vivo a polyclonal activation of murine B lymphocytes, followed by a marked increase in the production of immunoglobulin G2a (IgG2a). The role of T lymphocytes in this phenomenon was studied by injection of an anti-CD4 monoclonal antibody able to inhibit the T-helper function. This treatment profoundly depressed the production of IgG2a, whereas it had no effect on the proliferation of B cells. Activated B cells obtained from such inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…MHV is known to be lymphotropic and to induce diverse alterations of immune responses that depend on the mouse genetic background [5,20,21]. Thus, a model of MHV-induced anti-FAH autoAb was based on antigen mimicry -FAH N-terminal sequence is about 50% homologous with a MHV proteintogether with the alarm signals released by the MHV-injured liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MHV is known to be lymphotropic and to induce diverse alterations of immune responses that depend on the mouse genetic background [5,20,21]. Thus, a model of MHV-induced anti-FAH autoAb was based on antigen mimicry -FAH N-terminal sequence is about 50% homologous with a MHV proteintogether with the alarm signals released by the MHV-injured liver.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were inoculated intraperitoneally with 10 4 TCID 50 of MHV-A59 grown in NCTC 1469 cells [5]. Thirty days after the infection, the mice were injected intraperitoneally with 100 µl of mineral oil containing 0.16 µl of CCl 4 (dilution: 1:625).…”
Section: Viral Infection and Carbon Tetrachloride (Ccl4) Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was suggested that structural features of autoantigens, their locations, and catabolism during cell death and their translocation to cells that can present antigens to the immune system could contribute to selection of the autoimmune repertoire [16,17]. MHV is known to be lymphotropic and to induce diverse alterations of immune responses that depend on the mouse genetic background [1e4, 18,19], but why liver FAH was chosen as autoantigen among the large variety of liver proteins? As said by P. H Plotz [17]: ''The repertoire of target autoantigens is a wunderkammer e a collection of curiosities e of molecules with no obvious linking principle''.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses have been implicated in the generation of autoimmune disorders over the last 20 years [1e3]. It has been proposed that these infectious agents trigger an autoimmune humoral response by diverse mechanisms, including polyclonal B-lymphocyte activation, release of sequestered autoantigens (autoAg), antigenic mimicry, modification of self-antigen, epitope spreading of the anti-viral immune response or enhancement of major histocompatibility complex molecule expression [2,4,5].…”
Section: Introductionmentioning
confidence: 99%